Panda patrol : caring for a cub - Hatkoff, Juliana; Hatkoff, Isabella; Hatkoff, Craig (New York : Scholastic, 2012)
Examines the life of a panda cub at the Wolong Conservancy, explaining the measures that the conservancy's staff has taken in order to prepare the panda to be released into the wild at age two.
4.1
K-3
Keywords: Giant panda -- Juvenile literature; Pandas -- Juvenile literature; Giant panda; Pandas; Giant pandas; Pandas